Ratings of the emotional valence and arousal of collocations and their constituent words: How can they be useful in L2 vocabulary research?. (December 2019) - Lindstromberg, Seth
Abstract: Two dimensions of emotional meaning appreciably influence how well a lexeme is processed and remembered: valence (how pleasing) and arousal (how exciting). Although subjective, Likert-style ratings of such dimensions have a long history of fruitful use in experimental psychology—including psycholinguistics and bilingualism research—they have seldom figured in research of second language vocabulary acquisition. A literature review highlights reasons why this neglect is problematic. Fortunately, valence and arousal ratings are freely available for thousands of single words in a few languages. However, ratings of phrasal vocabulary items are rare. This study investigated how well the valence and arousal of two-word English collocations composed of content words can be estimated by proxy measures based on the rated valence and arousal of the constituent words. Evidently, genuine whole collocation ratings are needed. However, the square of the correlation between proxy ratings and genuine ratings estimates the degree to which the emotional content of collocations is compositional (i.e., predictable from the constituent words) meaning that, for emotional content, 1 - r 2 estimates the learning load of a typical collocation over and above the learning load of its constituent words. Finally, over 100 English MWEs are newly rated for valence and arousal. Highlights: Dimensions of emotional meaning (EM) influence L2 vocabulary learnability. Estimates of collocation EM are derivable from constituent words. Although substantially inaccurate, these estimates can be manifoldly informative. They enable estimation of collocation compositionality and extra learning burden. Over 100 English collocations are newly rated for emotional valence and arousal.